Caracterização do modelo de agroindustrialização de pequeno porte voltado à propriedade rural familiar do Município de Guarapuava - Pr - Nychai, Luci (2005)
This trial aimed on featuring small agro-industrialization from Guarapuava-PR, when familiar rural farms were inserted and highlighted some survival aspects at the market as a sustainable factor. It was taking into account the agroindustries survey, regarding feeding and non-feeding systems, which are part of secondary economical branch, as well as the small (1 to 50 hectares), rural and familiar farm profile, also integrated to cooperativeness. As a consequence, it was used a sample of 218 farms linked to Cooperative of Micro and Small Producers from Guarapuava and a confidential statistical level of 95% so, there was a 5 % of error. The insertion of agro-industrial units from The Program Farmer Factory was also considered. At the secondary sector, there are 70.83 % of enterprising units that belong to the non-feeding agro-industrial system and 29.17 % are from agro-feeding system, but 26.18 % of them have there production guided to agro-industrialization. The forest raw material is used in 64.59 % of agro-industries while 35.14 % of farming industries use it. Observing the familiar rural farms studied, it was possible to record that 26.60 % of them applied some king of agro-industrialization, formal or rudimental. Regarding, the Program Farmer Factory from 1999 to 2004, it was recorded 38 units, of them 2.63% in implantation and adjustment; 7.89 % in studied of economical viability; 7.89 % inactive; 10.53 % definitely closed and 71.05 % in activity. These results drive through a great challenge, which is the insertion of small familiar rural farm at the sustained agro-industrialization process, mainly because of the economical-financial aspect. The biggest difficulties were the absence technology; technical ability; competitiveness; strategic administration; quality and safety of products, but the most important was trading. Agro-industries enterprises by themselves do not show profitable results. The agricultureindustrialization development of small size, concerning the family rural farm, depends on the pattern set up by of formatted and strategic alliances through partnerships revealing a systemic pattern, as well as the necessity of working with several products due to the absence of scale production.